2020
DOI: 10.1093/jnci/djaa043
|View full text |Cite
|
Sign up to set email alerts
|

The Affordable Care Act’s Medicaid Expansion and Impact Along the Cancer-Care Continuum: A Systematic Review

Abstract: Abstract Background Health reform and the merits of Medicaid expansion remain at the top of the legislative agenda, with growing evidence suggesting an impact on cancer care and outcomes. A systematic review was undertaken to assess the association between Medicaid expansion and the goals of the Patient Protection and Affordable Care Act in the context of cancer care. The purpose of this arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
60
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 67 publications
4
60
3
Order By: Relevance
“…With the passing of the ACA, there has been a decrease in the rate of uninsured patients 32,33 as well as fewer patients with advanced cancer stages at diagnosis 34,35 in the states that have expanded Medicaid. This study adds to the ongoing body of research and the public health push for Missouri and other states to consider Medicaid expansion as a protection for their most vulnerable populations 36,37 . Furthermore, with research showing the effectiveness of patient‐focused breast cancer education programs 38,39 and the cost‐effectiveness of funding breast cancer screening programs, 40 furthering efforts to fund screening and education programs can further decrease disparities.…”
Section: Discussionmentioning
confidence: 90%
“…With the passing of the ACA, there has been a decrease in the rate of uninsured patients 32,33 as well as fewer patients with advanced cancer stages at diagnosis 34,35 in the states that have expanded Medicaid. This study adds to the ongoing body of research and the public health push for Missouri and other states to consider Medicaid expansion as a protection for their most vulnerable populations 36,37 . Furthermore, with research showing the effectiveness of patient‐focused breast cancer education programs 38,39 and the cost‐effectiveness of funding breast cancer screening programs, 40 furthering efforts to fund screening and education programs can further decrease disparities.…”
Section: Discussionmentioning
confidence: 90%
“…This trend is consistent with other studies that have shown that Medicaid expansion was associated with reduced socioeconomic disparity in insurance rates. 20 , 21 , 22 Importantly, our findings suggest that the downstream stage and treatment outcomes were also magnified in the low-income population. The fact that changes in the low-income population are associated with trends toward earlier diagnosis and receipt of indicated treatment suggests that expansion of insurance may be a valid mechanism to help reduce cancer disparity.…”
Section: Discussionmentioning
confidence: 63%
“…19 Previous research on the associations of Medicaid expansion with cancer care has focused on the association of expansion with the decreasing proportion of uninsured individuals rather than other aspects of cancer care, such as diagnosis and treatment. [20][21][22][23] Only a handful of studies have studied further downstream metrics, and they have identified small shifts to earlier stage disease in a few nongenitourinary cancers 21,22,24 and an increase in utilization of surgery for all cancers in aggregate. [25][26][27] However, these studies have generally been limited to only a year of postimplementation data, and the association of Medicaid expansion with alleviating racial/ethnic or socioeconomic disparity has been inconsistent between different subgroups and cancer types.…”
Section: Introductionmentioning
confidence: 99%
“…Levels and trends of mortality disparities could also reflect effects after earlier adoption of universal health coverage in Massachusetts compared with Pennsylvania. Current evidence suggests that the Medicaid expansion provision of the ACA succeeded in increasing insurance coverage as well as access to ambulatory and surgical cancer care, and possibly led to lower stage at presentation among low‐income populations, 12,39,40 but had less effect on the use of cancer prevention services and race/ethnicity disparities in access 39,41,42 . Massachusetts is a wealthier and more densely populated state than Pennsylvania, which also could have resulted in smaller absolute disparities based on race/ethnicity and nSEP.…”
Section: Discussionmentioning
confidence: 99%